Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pengusaha Kos - Elvana Sri Jannati Paputungan; Usman Moonti; Abdulrahim Maruwae; Meyko Panigoro; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The purpose of this study was to determine the effect of Business Capital, Business Location, Condition of Business Place on the Income of Boarding Entrepreneurs in Central City, Gorontalo City. This study uses a quantitative approach, with a total of 73 boarding houses in the middle city of Gorontalo. The main instrument used in this research is primary data in the form of research tools. The results showed that partially business capital had a significant positive effect on boarding house buyers, business location had a significant positive effect on boarding house buyers and business location conditions had a significant positive effect on boarding house buyers. Simultaneously, business capital, business location and business location conditions have a significant positive effect on the boarding house entrepreneur's income. The coefficient of determination (R2) is 0.447 or 44.7%.